Biodegradation of kraft lignin by a newly isolated anaerobic bacterial strain, Acetoanaerobium sp. WJDL‐Y2. (25th November 2015) - Duan, J.; Huo, X.; Du, W.J.; Liang, J.D.; Wang, D.Q.; Yang, S.C.
Abstract: An anaerobic kraft lignin (KL)‐degrading bacterial strain was isolated from sludge of a pulp and paper mill. It was characterized as Acetoanaerobium sp. WJDL‐Y2 by 16S rRNA gene sequencing. The maximum KL degradation capability of strain Y2 was determined to be 24·9% on a COD basis under an optimal condition with temperature of 31·5°C, initial pH of 6·8 and KL to nitrogen (as NH4 Cl) ratio of 6·5 by mass. Growth kinetic studies showed that the KL tolerance of strain Y2 was relatively high ( K i   = 8120·45 mg l −1 ). Analysing KL degradation products by GC‐MS revealed the formation of low‐molecular‐weight aromatic compounds (LMWACs), including benzene‐propanoic acid, syringic acid and ferulic acid. This indicates that strain Y2 can oxidize lignin structure's p‐hydroxyphenyl (H) units, guaiacyl (G) units and syringyl (S). In addition, the inoculated sample also contained low‐molecular acid compounds, such as hexanoic acid, adipic acid and 2‐hydroxybutyric acid, further validating strain Y2's ability to degrade KL. Significance and Impact of the Study: Kraft lignin containing effluents discharged from pulp and paper industries causes serious environmental pollution in developing countries. Due to the immense environmental adaptability and biochemical versatility, bacterial ligninolytic potential deserve to be studied for application in effluent treatment of pulp and paper industry. In this study, an anaerobic lignin‐degrading bacterium, Acetoanaerobium sp. WJDL‐Y2 (accession no.KF176997 ), was isolated from the sludge of a pulp and paper mill. Strain Y2 can play an important role in treating pulp and paper wastewater, as well as breaking down materials for biofuel and chemical production. Abstract : Significance and Impact of the Study: Kraft lignin containing effluents discharged from pulp and paper industries causes serious environmental pollution in developing countries. Due to the immense environmental adaptability and biochemical versatility, bacterial ligninolytic potential deserve to be studied for application in effluent treatment of pulp and paper industry. In this study, an anaerobic lignin‐degrading bacterium, Acetoanaerobium sp. WJDL‐Y2 (accession no.KF176997 ), was isolated from the sludge of a pulp and paper mill. Strain Y2 can play an important role in treating pulp and paper wastewater, as well as breaking down materials for biofuel and chemical production.